Non-stationarity and stage-of-the-business-cycle effects in consumption-based asset pricing relations - Ferson, Wayne E.; Merrick, John J. (Journal of Financial Economics, 1987)
Empirical tests of Euler equations relating security returns and consumption usually appear to reject the model. Using a common specification of aggregate preferences and instrumental variables, this paper examines some potential reasons for rejections. The evidence indicates that maintained stationarity assumptions of previous tests fail for post-war U.S. quarterly and monthly data. Shifts in model parameters are found across policy regimes (pre-1951 and post-1979) and across stages of the business cycle (recession versus non-recession). Controlling for some of these factors, less evidence is found against a simple consumption-based asset pricing model in non-recession periods.